Resistance to Love in Medieval English Romance : Negotiating Consent, Gender, and Desire. - Piercy, Hannah (Woodbridge : Boydell & Brewer, Limited, 2023)
This book explores resistance as a widespread motif in medieval romance to consider themes of consent, gender, and desire in medieval England.
Front cover -- Contents -- Acknowledgements -- Abbreviations -- Introduction -- 1 'Ar ye a knyght and ar no lovear?' Men Who Resist Love -- 2 'But of love to lere': The Proud Lady in Love -- 3 'Ne feolle hit þe of cunde / To spuse beo me bunde': Resisting Mésalliance -- 4 'What wonder is it thogh she wepte'? Hierarchies of Desire, Race, and Empathy -- 5 'What deyntee sholde a man han in his lyf / For to go love another mannes wyf'? Resisting Adultery, Resisting Rape Culture -- Conclusion: The Ends of Romance -- Bibliography -- Index -- Volumes Already Published.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books